Self organizing maps and bit signature: A study applied on signal language recognition - Neris, Marrony N.; Silva, Alexandre J.; Peres, Sarajane M.; Flores, Franklin C. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Self Organizing Map (SOM) is a kind of artificial neural network with a competitive and unsupervised learning. This technique is commonly used to dataset clustering tasks and can be useful in patterns recognition problems. This paper presents an artificial neural network application to signals language recognition problem, where the image representation is given by bit signatures. The recognition results are promising and are presented in this paper. More, some analysis about the combination SOM + bit signature improved our understanding about the characteristics of the LIBRAS signals and the conclusions are also listed in this paper. © 2008 IEEE.